Trends in the Use of Interactive E-Modules in Ecology Learning - Raihan, Raden Muhammad; Sari, Indah Juwita; Alasa, Victor M. (International Journal of Biology Education Towards Sustainable Development, 2025)
This study aimed to analyze the trend of interactive e-module usage in Ecology learning and identify the gap between students' needs and experiences of using them. The research method used a mixed-method research design by combining Systematic Review and quantitative descriptive method, reinforced by student needs questionnaire data. The results of the study indicate that students' needs and interests in interactive e-modules are in the high category, especially for visual and interactive learning media. However, the experience of using interactive e-modules is still relatively low. This finding indicates a gap between students' needs and the implementation of e-modules in Ecology learning. Therefore, the development and implementation of interactive e-modules that are appropriate to students' needs need to be optimized to support more effective Ecology learning.